Respuesta :

Answer:

y = 3x = 1

Step-by-step explanation:

Answer:

y = 3x - 1

Step-by-step explanation:

Check. Plug in the given x, and see if the result is the given y:

y = 3x - 1

When: (x = 8 , y = 23)

23 = 3(8) - 1

23 = (3 * 8) - 1

23 = (24) - 1

23 = 23 (True).

When: (x = 2 , y = 5)

5 = 3(2) - 1

5 = (3 * 2) - 1

5 = 6 - 1

5 = 5 (True)

When: (x = -3 , y = -10)

-10 = 3(-3) - 1

-10 = (3 * -3) - 1

-10 = (-9) - 1

-10 = -10 (True).

When (x = 9 , y = 26)

26 = 3(9) - 1

26 = (3 * 9) - 1

26 = (27) - 1

26 = 26 (True).

When you graph, simply graph the given points (bolded) onto the graph.